2018
DOI: 10.1093/nar/gkx1298
|View full text |Cite
|
Sign up to set email alerts
|

PIDD mediates the association of DNA-PKcs and ATR at stalled replication forks to facilitate the ATR signaling pathway

Abstract: The DNA-dependent protein kinase (DNA-PK), consisting of the DNA binding Ku70/80 heterodimer and the catalytic subunit DNA-PKcs, has been well characterized in the non-homologous end-joining mechanism for DNA double strand break (DSB) repair and radiation resistance. Besides playing a role in DSB repair, DNA-PKcs is required for the cellular response to replication stress and participates in the ATR-Chk1 signaling pathway. However, the mechanism through which DNA-PKcs is recruited to stalled replication forks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…2). This is consistent with our findings that DNA-PKcs is critically involved in the cellular response to replication stress, and it coordinates with the ATR signaling pathway for optimal replication checkpoint and fork recovery [75,81,111].…”
Section: Dna-pk Coordinates With Topoisomerase-ii To Resolve Stalled supporting
confidence: 93%
See 1 more Smart Citation
“…2). This is consistent with our findings that DNA-PKcs is critically involved in the cellular response to replication stress, and it coordinates with the ATR signaling pathway for optimal replication checkpoint and fork recovery [75,81,111].…”
Section: Dna-pk Coordinates With Topoisomerase-ii To Resolve Stalled supporting
confidence: 93%
“…It is possible that Ku and DNA-PKcs contribute to the telomeric capping and maturation process in distinct ways. For example, DNA-PKcs is required to resolve the stalled replication fork in telomeres and participates in replication stress signaling independently of Ku [75,76].…”
Section: Involvement Of Dna-pkcs Kinase Activity and Its Thr2609 Clusmentioning
confidence: 99%
“…It is unclear how our respective studies could come to such different conclusions at this point, so further replication studies will be required in future. Furthermore, it has been suggested that DNA-PKcs also plays roles in responses to stalled replication forks besides DSB repair 38,39 . Our mass spectrometry and ensuing immunoprecipitation analysis indicated that UCHL3 could interact with DNA-PKcs, possibly suggesting context specific functions of UCHL3 for maintaining genome integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of replication stress, it was shown that ATR phosphorylates DNA-PK following UV-induced replication stress and that the DNA-PK function facilitates DNA damage resolutions [310]. The phosphorylation of DNA-PK can reinforce the ATR-Chk1-mediated DDR by promoting a claspin-Chk1 interaction stability, and it was proposed that DNA-PK may act as a signal amplifier of ATR [311,312]. Moreover, upon ATR inhibition, DNA-PK can act as a backup pathway that phosphorylates Chk1 and other targets, suppressing origin firing [299].…”
Section: Dna-pkmentioning
confidence: 99%